A Review of the Effects of Natural Compounds, Medicinal Plants, and Mushrooms on the Gut Microbiota in Colitis and Cancer - Cheung, Man Kit; Yue, Grace Gar Lee; Chiu, Philip Wai Yan; Lau, Clara Bik San (Frontiers in Pharmacology, 2020)
The human gastrointestinal tract harbors a diverse array of microorganisms that play fundamental roles in health and disease. Imbalance in the gut microbiota, namely dysbiosis, can lead to various diseases, including cancer and gastrointestinal tract disorders. Approaches to improve gut dysbiosis, such as dietary intervention, intake of probiotics, and fecal microbiota transplantation are emerging strategies to treat these diseases. Various medicinal botanicals have reported anti-cancer and/or anti-inflammatory properties. Preclinical studies have illustrated that some of these natural products are also capable to modulate the gut microbiota, suggesting their use as possible alternative approach to improve gut dysbiosis and thereby assist diseases treatment. In this review article, we have summarized the current knowledge on the effects of natural compounds, medicinal plants and mushrooms on the gut microbiota in various cancers and colitis in preclinical animal models. Challenges towards the clinical use of these medicinal botanicals as modulators of the gut microbiota in cancer and colitis treatment are also discussed.